Correction: Huang et al. Next Generation of Computationally Optimized Broadly Reactive HA Vaccines Elicited Cross-Reactive Immune Responses and Provided Protection against H1N1 Virus Infection. Vaccines 2021, 9, 793 - Ying Huang; Monique S. França; James D. Allen; Hua Shi; Ted M. Ross (Vaccines)
The authors would like to make the following corrections to this published paper [...]